Metagenomic dna isolation from sheep feces and pcr detection of several rumen bacteria - Arif Yavuz; Dilek Özgün Ekiz; İlhami Kenger; Uğur Çömlekcioğlu (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to isolate metagenomic DNA from fresh and dry sheep feces and to detect several rumen bacteria using the specific primers. Materials and Methods: The metagenomic DNA isolation was performed by using commercial I-Genomic Stool DNA Isolation Kit. Anaerovibrio lipolytica, Fibrobacter succinogenes, Prevotella bryantii, Prevotella ruminicola, Ruminobacter amylophilus, Ruminococcus albus, Ruminococcus flavefaciens, Streptococcus bovis, Selenomonas ruminantium and Succinovibrio dextrinosolvens were screened using metagenomic DNA with polymerase chain reaction and spesific primers. Reaction of 16S rRNA region with SphI was carried out to confirm the absence of R. amylophilus, R. albus and S. dextrinosolvens. Results: Fecal samples dried rapidly and lost its 53.72% of fresh mass. After the DNA isolations from fresh and dried samples, DNA concentrations and purity were varied between 25.60-59.50 ng/μL and 1.72-1.90, respectively. It was observed that fecal inhibitors had no effect on PCR. A. lipolytica, F. succinogenes, P. bryantii, P. ruminicola, R. flavefaciens, S. bovis and S. ruminantium were detected with specific primers however PCR did not reveal the presence of R. amylophilus, R. albus and S. dextrinosolvens. SphI digestion of 16S rDNA regions has confirmed this result. Conclusions: In this study, effect of drying in natural conditions on metagenomic DNA isolation from fecal samples was determined. Furthermore, PCR detection of several rumen bacteria was performed by using isolated DNA. In conclusion, it may be stated that the metagenomic DNA isolated from dried fecal samples could be an effective tool for the detection of bacterial populations.